Persepsi Penonton Drama Korea Doctor Slump dalam Membentuk Kepercayaan Diri - Dwinanda, Devina Adilah; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The development of globalization progress today has brought about major changes in interaction between countries, especially through the spread of global media. The culture of various countries are becoming increasingly diverse and widespread. The Korean entertainment industry has also experienced tremendous development as seen from the Korean Wave phenomenon that is now spreading increasingly throughout the world. As a result, Korea is becoming increasingly famous around the world, it’s culture, food, clothing and various related elements are quickly becoming global trend. Korean drama is one of the major impacts of the Korean Wave. The purpose of this study is to analyze and explain the verbal communication messages contained in the Korean Drama Doctor Slump and how these messages can build self- confidence. The concepts used in this study include popular culture, verbal communication, SOR theory and building self-confidence. The results of this study indicate that the messages in the Korean drama that the audience gets is about symbolic reinforcement. Moral messages such as family, friendship, hard work, and mental health have a strong impact on the audience. Perkembangan kemajuan globalisasi saat ini membawa perubahan besar dalam interaksi antar negara terutama melalui penyebaran media global. Budaya berbagai negara menjadi semakin beragam dan tersebar luas. Industri hiburan Korea juga mengalami perkembangan yang luar biasa terlihat dari fenomena Korean Wave yang kini menyebar semakin seluruh dunia. Hasilnya Korea menjadi semakin terkenal di seluruh dunia, budaya, makanan, pakaian serta berbagai elemen terkaitnya dengan cepat menjadi trend global. Drama Korea yaitu salah satu dampak besar dari Korean Wave. Tujuan penelitian ini adalah untuk menganalisis dan menjelaskan pesan komunikasi verbal yang terdapat pada drama Korea Doctor Slump dan pesan tersebut dapat membangun kepercayaan diri. Konsep yang digunakan dalam penelitian ini meliputi budaya populer, komunikasi verbal, teori SOR dan membangun kepercayaan diri. Hasil penelitian ini menunjukkan bahwa pesan dalam drama Korea yang di dapat terhadap penonton tentang penguatan simbolik. Pesan moral seperti keluarga, persahabatan, kerja keras dan kesehatan mental yang memberikan dampak kuat bagi penonton.